2021
DOI: 10.3390/ijerph182312557
|View full text |Cite
|
Sign up to set email alerts
|

New Self-Report Measures of Commuting Behaviors to University and Their Association with Sociodemographic Characteristics

Abstract: Active commuting provides an opportunity for increased physical activity levels by a simple, inexpensive, and easy way to be incorporated in daily routines and could be considered a steppingstone for achieving a sustainable society since it provides physical, psychological, environmental, and economic benefits. Objective: (a) to describe the commuting patterns to and from university in students regarding gender, (b) to provide new self-report variables to measure the active commuting behavior, and (c) to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Participants provided information on the location from which they commute, and these data were spatially distributed using QGIS 3.22.9 (QGIS Development Team; URL: https://qgis.org/en/site/, accessed on 18 July 2022). Since respondents' addresses were not collected, the Euclidean distance between the centroids of the indicated neighborhoods and the center of the BCTF was calculated when analysing the data from the second survey [51]. The study population was then aggregated by four zones as illustrated in Figure 1 and presented in Table 1b.…”
Section: Data Processingmentioning
confidence: 99%
“…Participants provided information on the location from which they commute, and these data were spatially distributed using QGIS 3.22.9 (QGIS Development Team; URL: https://qgis.org/en/site/, accessed on 18 July 2022). Since respondents' addresses were not collected, the Euclidean distance between the centroids of the indicated neighborhoods and the center of the BCTF was calculated when analysing the data from the second survey [51]. The study population was then aggregated by four zones as illustrated in Figure 1 and presented in Table 1b.…”
Section: Data Processingmentioning
confidence: 99%
“…A healthy and active lifestyle has numerous benefits for people’s physical and mental health ( Palma-Leal et al, 2021 ; Chillón et al, 2021 ). Physical activity can be defined as any skeletal movement produced by muscle contraction that results in significant energy expenditure ( Escalante, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main health message directed to all populations is that doing some PA is better than doing none [ 2 , 12 ]. Active commuting (AC), such as walking or cycling, provides an opportunity for increased PA levels in university students by increasing energy expenditure per minute [ 13 ]. In addition, a systematic review demonstrated that children and adolescents who walk or cycle to school can accumulate between 5 and 37 additional minutes of PA per day compared to those using passive modes of commuting [ 14 ].…”
Section: Introductionmentioning
confidence: 99%